Effect of cystamine on sperm and antioxidant parameters of ram semen stored at 4 °C for 50 hours - J., Jumintono; S., Alkubaisy; D., Yánez Silva; K., Singh; A., Turki Jali; S., Mutia Syarifah; Y., Fakri Mustafa; I., Mikolaychik; L., Morozova; M., Derkho (Razi Vaccine & Serum Research Institute, 2021)
Physical and chemical changes caused by oxidative stress in the spermatozoa membrane can reduce spermatozoa function and even lead to death. Cystamine (NH2-CH2-CH2-SH, β-mercaptoethylamine) is a natural substance that modulates the endocrine and metabolic status of animals. This substance has antioxidant and anti-apoptotic effects by inducing intracellular cysteine accumulation. Cystamine is used to treat many diseases despite its many side effects. Sheep semen is sensitive to the stressful condition of chilling storage, which restricts semen storage for artificial insemination in commercial herds. The effect of cystamine on spermatogenesis is not yet fully understood. The present study aimed to investigate the effect of cysteamine addition to the sheep sperm extender during cooling storage on semen quality parameters. Sperm samples were collected from six Edilbayevskaya rams (2 and 3 years old, 70-85 kg). The samples were diluted by extender and supplemented with different concentrations of cysteamine (0, 1, 2, 5, and 10 mM) and cooled to 4ºC for 50 h. Motility parameters, membrane integrity, viability, lipid peroxidation, and mitochondrial activity of cooled semen were evaluated at 0, 25, and 50 h of cooling storage. Although cysteamine failed to affect semen quality at start time (0 hrs), extender supplementation with cysteamine improved sperm total motility, progressive motility, and mitochondrial membrane potential during storage periods (P≤0.01). Moreover, using 1 and 2 mM cysteamine functionally and viably improved (P≤0.01) sperm membrane compared to other treatments. Antioxidant potential (AOP), lipid peroxidation (LPO), and total glutathione (tGSH) (except AOP at 50 h) were significantly different after semen storage at 4 °C. Therefore, levels of AOP and tGSH were significantly increased by using cysteamine. Cysteamine supplementation (1 and 2 mM cysteamine) leads to lower levels of LPO (p<0.01) at 0, 25, and 50 h. Therefore, finding and using the best concentrations of cysteamine in a cooling extender could be effective in saving sheep semen against damages of the cooling storage process.